A grand design for peace and reconciliation achieving Kyosei in East Asia - Murakami, Yōichirō 1936-; Schoenbaum, Thomas J. (Edward Elgar Publishing Limited, 2008)
Scholars from Japan and a range of other countries explore in this book the still-unfinished effort to achieve the reconciliation of old enmities left over from past wars in East Asia